Teaching science in the 21st century - Rhoton, Jack.; Shane, Patricia (b, 2017)
The collection of 21 provocative essays gives you a fresh look at today's most pressing public policy concerns in science education, from how students learn science to building science partnerships to the ramifications of the No Child Left Behind legislation.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching -- United States; Science teachers -- In-service training | -- United States